Rancang Bangun Kursi Roda Elektrik untuk Disabilitas Berbasis Microkontroler Atmega 328 - Badrul Wajdi; Sapiruddin Sapiruddin; Tsamarul Hizbi; Sudaisi Hafizin (Universitas Hamzanwadi, 2021)
The purpose of making this tool is to design and manufacture an electric wheelchair for disabilities based on the ATMega328 microcontroller. This tool is expected to make it easier for users who use wheelchairs to be able to use them independently. The design of an electric wheelchair for disabilities based on the ATmega328 microcontroller consists of several stages starting from the needs identification stage, needs analysis, circuit design, tool modification, program flowchart, tool evaluation, and data collection. The main components used as the main control are Arduino UNO (ATMega 328), joystick as control medium, DC driver as rotation regulator, and DC motor as wheelchair propulsion. Based on the test results, the results of the control experiment using a joystick and a microcontroller produce the wheelchair movement output according to the instructions that have been set as input. The wheelchair can move with instructions, Forward, Backward, Left, Right, and Stop. The wheelchair can carry a maximum user load of 25 kg, plus a battery load and a DC motor of 25 kg, a total load that can be carried is 50 kg. The results of testing the performance of the system can work in accordance with its functions and objectives.